Estimation of the Status of Small-Scale Fisheries Resources in Semarang City: Pendugaan Status Sumberdaya Perikanan Skala Kecil di Kota Semarang (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2021)
Fisheries in Semarang City are dominated by small-scale fisheries. This is indicated by the use of the largest fishing fleet of 10 gross tons operating near the coast. Fisheries statistics for 10 years (2010-2019) show that fishery catches have begun to decline, while the number of fishing units have increased. This indicates that fish stocks are starting to decrease and the level of utilization of fisheries resources leads to overfishing. This is supported by the results of direct observation in the field which showed that the number of catches tends to be small and the size of caught fish tends to be small. This study aims to analyze the status of small-scale fisheries in Semarang City. The method used in this study is the analysis of time series surplus production, namely data from the catch (ton/year) and the number of fishing gear (unit) within 10 years (2010-2019), to calculate the catch per-unit effort (CPUE), maximum sustainable yield (MSY), optimum effort (fopt), utilization rate (TP) and capacity level (TK). This study was obtained results of a downward trend in CPUE; the existing fishery catch or production in 2019 has exceeded the MSY value is 479 tons/year (Schaefer) and 439.11 tons/year (Fox); utilization rate of more than 100% which is 108-127% (Schaefer) and 118-138% (Fox), so that small-scale fisheries in Semarang City are at the level of over-exploited. Based on the fopt analysis, the number of fishing gear used (fexisting) has exceeded the optimum effort with a fishing capacity exceeding 100%, so that small-scale fisheries in Semarang City have experienced overcapacity.